Influence of Branded Entertainment and Non-Promotional Educational Content on TikTok toward Gen Z’s Perception and Purchase Intention - Robi Rojaya Simbolon; Farrel Pasya Harramain; Adinda Dwi Handayani; Elena Elizabeth Simbolon; Sania Aryani (SAINTIS Publishing, 2025)
This study aims to analyze the influence of branded entertainment series (BES) and non-promotional educational content (NPEC) on positive perceptions and purchase intentions among Generation Z, focusing on TikTok users in the Bandung Raya area. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), this research involved 113 respondents, consisting of Generation Z students actively using the TikTok application. The analysis revealed that BES has a significant positive impact on purchase intentions, although its effect on positive perceptions is relatively smaller. Conversely, NPEC demonstrated a stronger influence on positive perceptions and was also significant in affecting purchase intentions. These findings indicate that while BES effectively increases purchase intentions, NPEC plays a more significant role in shaping positive brand perceptions, ultimately influencing consumer purchase decisions. Positive perceptions were found to mediate the relationship between BES, NPEC, and purchase intentions, confirming the importance of building a good brand image as a preliminary step to influencing purchasing decisions. This study provides valuable insights for marketers in designing more effective marketing strategies, especially on social media platforms like TikTok, which are highly popular among Generation Z. By understanding the impact of BES and NPEC, brands can more accurately choose the content strategies to build stronger and more authentic relationships with young audiences.